Attitude Towards and Adoption of the Novel Learning Environment Among Undergraduate Medical Students During COVID-19 - Mohr, Sonja; Küfe, Birgit; Rheingans, Anke; Guse, Jennifer (Frontiers in Education, 2021)
Higher education has changed significantly since the beginning of the CoViD-19 pandemic. Medical education programs with extensive practical and interactive components faced major challenges to protect students, faculty and patients. In response to CoViD-19, many medical schools worldwide shut down undergraduate medical education and converted most of their teaching to digital formats. The aim of this paper is to assess the attitude towards and adoption of the novel learning environment among undergraduate medical students during CoViD-19. Two studies were conducted to analyze specific aspects of the adaption of digital teaching during the digital summer semester 2020 (study 1), and to compare student satisfaction and their feeling of preparedness for exams in the digital semester compared to traditional semesters (study 2). Results show that there are numerous pros and cons of digital teaching. Pros were the large flexibility and large-scale availability of digital teaching materials. Cons were the lack of interactions with peers, professionals and patients in practice. Results also show that female students as well as year 1 students seemingly coped better with the digital learning environment. Students with childcare or job obligations also benefited from the large flexibility. While student satisfaction decreased in the digital semester, they did not feel less prepared for exams. Cross-sectional comparisons revealed that student satisfaction and agreement gradually decreased in the comparison of the different cohorts with fourth year students being the least satisfied and showing the least agreement regarding the feeling of preparedness for exams. Altogether, our results indicate that students were able to cope with digital teaching, but clearly, some groups of students were able to better adapt to the novel learning environment. This might demand the introduction of tailored educational support services for different groups of students during CoViD-19 as they progress through medical school.